Elemento para el tratamiento de paciente con retardo y retraso del lenguaje del área de fonoaudiología de la fundación CIREC en la ciudad de Bogotá. (2021)
Taking into account the user whom I worked with, furthermore,In this project our subject is represented by kids with special needs between 2 and 6 years old.work is carried out from a context-based on rehabilitation through associative learning. Consequently it developed work from rehabilitation through associative learning. Developing a performance on a therapeutic matter in intensive language therapy at Circe foundation in Bogotá, where it could be established an ergonomic and antropométrica of the space in relation with the body, highlighting the conceptual use of the sinapais as a media of exchange and evolution of the data which is translated Into levels learning . It describes how it is performed by a divided environment in biomass which executes high complex levels within information into the modules. From a design perspective based on the analysis and prototype, getting as a result an element based on the sea environment where every step and section represents an element or an animal that through specific activities for the learning practice to reinforce the expression and language comprehension. Along with the concept the use of sensorial resources such as lights and songs as an interactive media between the subject and the environment. These strategies propose an intervention with the subject in a dynamic and entertaining way. For the purpose of that it will be applicable in the future as a community support in the rehabilitation towards either subjects or patients. Therefore depending on the patient needs it will be dictated and autonomy form the specialist to organize every activity described